Food safety concepts of food handlers in selected urban community - Castillejos, Jennyfer Jinky M.
The study was conducted to determine the concept of food safety of household food handlers. Thirty one (31) food handlers coming from UP BLISS households participated in the study. Qualitative design was utilized in the study with the use of a 10-item, open-ended questionnaires, written in Filipino regarding food safety characteristics of safe and unsafe food, personal hygiene, safe food handling practices and effect of unsafe food. Content analysis was used to analyze the data using categories identified based on the responses. The study revealed that6 the respondents had a basic but limited concept of food safety. Their concept centered mostly on cleanliness - cleanliness in handling the food, in the preparation area, utensils, ingredients, food handler, storage areas and the source or ingredients. Respondents realize the precarious state of raw food like meat, seafoods, vegetables or fruits. There was also recognition that street foods are not safe. Majority of the respondents perceived food handlers to be the cause of unsafe food, however, they had limited concept of proper food handler's hygiene, mostly centering on hand washing. Respondents were also not able to distinguish differences between the concepts of food handler's hygiene and proper handling practices. There were also some respondents who could not delineate between the concepts of nutritious foods and food safety.